Comprehensive study on intrinsic combustion behavior of non-premixed coal-biomass pellet at rapid heating rate. (1st March 2021) - Li, Hanjian; Chi, Huanying; Hu, Song; Wang, Yankui; Song, Gongxiang; Abdulmajid, Abdullahi Shagali; He, Limo; Wang, Yi; Su, Sheng; Xiang, Jun
Abstract: Non-premixed pelletization was proposed in low-cost coal-biomass pellet production for Circulating Fluidized Bed combustors. A novel non-premixed pelletization structure C-B-C (coal-biomass-coal) was proposed according to simulation results. Comprehensive study on the combustion behaviour of non-premixed coal-biomass pellet with such structure was carried out at heating rate over 200 ℃/s in a concentrating photothermal reactor. The result showed that the addition of biomass in non-premixed coal-biomass pellet could promote the combustion process but also cause slagging. The addition of biomass significantly increased the reaction index of the whole combustion process while the activation energies during devolatilization to ignition decreased linearly from 47.44 kJ/mol to 23.18 kJ/mol. Biomass promoted CO generation, increased NO emission (due to higher N content and lower chamber temperature) and decreased SO2 emission, during the combustion of non-premixed coal-biomass pellets. The feasibility of coal-biomass non-premixed pelletization method was verified.